Can a bronchoscopist reliably assess a patient's experience of bronchoscopy? - Hasmoni, Mohamed Hadzri; Mohd Shah, Azarisman Shah; Abdul Rani, Mohammed Fauzi; Harun, Roslan; Abdul Manap, Roslina; Tajudin, Nor Adina; Mohd. Anshar, Fauzi (Royal Society of Medicine Press, 2010)

(untitled)
OBJECTIVES: Bronchoscopy is an essential investigative tool in many respiratory complaints. The procedure can be unpleasant for both bronchoscopists and patients. To the best of our knowledge, there are only a few studies that correlate the bronchoscopist's satisfaction with that of the patient's during bronchoscopy. The aim of our study is to assess whether or not a bronchoscopist could reliably assess a patient's satisfaction during bronchoscopy.